Soil erosion and environmental degradation in Nepal: A Review of Environmental Policies - Raya, Balaram (The Third Pole: Journal of Geography Education, 2023)
Soil erosion is a natural process that occurs more frequently in mountainous regions in the Himalayas due to the complex landforms. Nepal also experiences severe forms of soil erosion due to its geographical complexity. This study examines the issues of soil erosion in relation to the environment and evaluates the effectiveness of existing environmental policies in Nepal, using secondary sources of data. The study reveals that Nepal has an average annual soil erosion rate of 25 tons per hectare per year, resulting in the total annual loss of 369 metric tons. This rate is higher compared to other areas around the world. The middle mountain region of Nepal has a higher mean annual soil erosion rate per hectare per year (which is of 38.4 tons) than other physiographic regions. Soil erosion is caused by various factors such as rainfall, water flow, land cover, geographical setting, and conservation practices – which leads to a decrease in agricultural productivity. Both on-site and off-site effects pose a significant risk to agriculture, development projects and the environment. It is suggested that the steps have to be taken to the environmental safeguard for reducing soil erosion and mitigate the problem through government agencies by emphasizing on effective implementation measures of the existing environmental policies, regulations, and development plans.